Complexity and Organizational Communication: A Quest for Common Ground. (June 2016) - Poutanen, Petro; Siira, Kalle; Aula, Pekka
In recent years, a growing body of literature has emerged from the intersection of complex systems science and organizational communication. However, due to the incoherence and immaturity of complexity science, this body of research is slightly disorganized. This article explores this research node using a meta-paradigmatic framework to untangle and clarify the different paradigmatic assumptions in the field of organizational communication research that has adopted the complexity science perspective. Our analysis reveals five research clusters that differ from each other in their understanding of what complexity is and in how they define communication. Based on our analysis, we present suggestions for finding common ground and point the way towards a future research agenda in complexity-based research in the areas of organizational communication and human resource development (HRD). In addition, we discuss the implications and possibilities that the complexity perspective can offer for HRD in practice.